Vaccine Hesitancy in the Administration of Hepatitis B Birth Dose Immunization to Newborns: A Parental Belief Perspective - Fitriana Al Hidayah; Hayun Manudyaning Susilo; Nur Hidayati (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
Vaccine hesitancy in newborn immunization has become an important concern in maternal and child health services, particularly in the administration of Hepatitis B birth dose immunization. However, research specifically addressing parental belief as a determinant of refusal or delay in Hepatitis B0 immunization remains limited. This study aimed to describe vaccine hesitancy in the administration of Hepatitis B birth dose immunization to newborns from the perspective of parental belief. A qualitative approach with a descriptive case study design was employed, involving one postpartum mother and her newborn selected through purposive sampling. Data were collected through anamnesis, observation, physical examination, neonatal care documentation, and midwifery records. The data were analyzed descriptively by comparing clinical findings with relevant immunization standards and theoretical concepts of vaccine hesitancy. The findings indicate that the newborn was clinically stable, born at term, and received essential newborn care, including eye ointment and vitamin K1 injection. However, Hepatitis B0 immunization was refused by the mother on the basis of family belief, despite the provision of health education and informed consent. This case demonstrates that vaccine hesitancy in neonatal care may be shaped not only by access to services or clinical eligibility but also by belief-based and trust-related considerations within the family. The study concludes that parental belief plays a critical role in decisions to refuse Hepatitis B0 immunization for newborns. These findings contribute to the literature on vaccine hesitancy in maternal and child health by providing case-based insight into belief-driven immunization refusal and offer practical implications for midwives and health workers to provide earlier, empathetic, and culturally sensitive counseling during antenatal care.